2023
DOI: 10.15576/asp.fc/2023.22.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Farmers’ Perceptions Concerning Potato Farming Systems in North Western Ethiopia

Abstract: Aim of the study Assessing the perception of north western Ethiopia farmers’ on the role of potato in the farming system Material and methods: Elders with different socioeconomic back grounds and experience on potato production were used for this study. A proportional allocation formula was employed. Data was collected from both primary and secondary sources. Primary sources of data were collected. The questionnaire constituted open ended questions to allow full expression about the issue. Discussions were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Barghi et al (2012) reported that the varieties with the highest tuber dry mass at early stages were Guassa and Belete varieties, at 75 DAP. In areas where erratic rainfall is expected, meaning that potato is an ideal crop for production there, Aragaw et al (2023), Guassa and Belete varieties can be used for production. Dagim variety was severely affected by late blight disease, resulting in the lowest TDM, LAI, CGR TGR at 75 DAP, and low yield.…”
Section: Discussionmentioning
confidence: 99%
“…Barghi et al (2012) reported that the varieties with the highest tuber dry mass at early stages were Guassa and Belete varieties, at 75 DAP. In areas where erratic rainfall is expected, meaning that potato is an ideal crop for production there, Aragaw et al (2023), Guassa and Belete varieties can be used for production. Dagim variety was severely affected by late blight disease, resulting in the lowest TDM, LAI, CGR TGR at 75 DAP, and low yield.…”
Section: Discussionmentioning
confidence: 99%